LARVAS DE HYSTEROTHYLACIUM SP (NEMATODA: RAPHIDASCARIDIDAE) EN EL PEZ VOLADOR EXOCOETUS VOLITANS LINNAEUS, 1758 (EXOCOETIDAE, BRUUN, 1935)) LIMA, PERÚ - Naupay, Asucena (2020)
Anisakidosis is an infection caused mainly by Anisakis simplex (Rudolphi, 1809), Pseudoterranova decipiens (Krabbe, 1878) Gibson, 1983 and very low frequency around the world by Contracaecum osculatum (Rudolphi, 1802) Baylis, 1920 and Hysterothylacium aduncum (Rudolphi, 1802). In Peru, Deardorff & Overstreet, 1982 en has been identified in Coryphaena hippurus Linnaeus, 1758, but there is no record of the morphometric characteristics of third instar larval stages in smaller teleost fishes. Given the importance of the flying fish Exocoetus volitans Linnaeus, 1758 in the trophic chain of C. hippurus, we believe that this fish would have a very important role in the biological cycle of Hysterothylacium sp. as a paratenic host. The objective of the present work was to identify the morphometric characteristics of the nematode larvae found in E. volitans and to determine their prevalence (P), mean intensity (IM) and mean abundance (AM). The sample consisted of 51 specimens of E. volitans, which were acquired in the fishing terminal of the district of Ventanilla, Callao. The collection and identification was done applying conventional methods and techniques. The presence of third stage larvae of Hysterothylacium sp. in gills and intestine is located mainly in the visceral surface and muscle tissue of E. volitans. Infected fish showed a prevalence of 90% (46/51), mean intensity of 58 with an intensity range of (1 - 1720) and a mean abundance of 52.11. Third stage larvae of Hysterothylacium sp. and parasitic indexes in E. volitans are identified for the first time in Peru.